Proteomic Analysis of a Syntrophic Coculture of Syntrophobacter fumaroxidans MPOBT and Geobacter sulfurreducens PCAT - Mollaei, Monir; Suarez-Diez, Maria; Sedano-Nunez, Vicente T.; Boeren, Sjef; Stams, Alfons J. M.; Plugge, Caroline M. (Frontiers in Microbiology, 2021)
We established a syntrophic coculture of Syntrophobacter fumaroxidans MPOBT (SF) and Geobacter sulfurreducens PCAT (GS) growing on propionate and Fe(III). Neither of the bacteria was capable of growth on propionate and Fe(III) in pure culture. Propionate degradation by SF provides acetate, hydrogen and/or formate that can be used as electron donors by GS with Fe(III) citrate as electron acceptor. Proteomic analyses of the SF-GS coculture revealed propionate conversion via the methylmalonyl-CoA (MMC) pathway by SF. The possibility of interspecies electron transfer (IET) via direct (DIET) and/or hydrogen/formate transfer (HFIT) was investigated by comparing the differential abundance of associated proteins in SF-GS coculture against i) SF coculture with Methanospirillum hungatei (SF-MH), which relies on HFIT, ii) GS pure culture growing on acetate, formate, hydrogen as propionate products and Fe(III). We noted some evidence for DIET in the SF-GS coculture i.e. GS in the coculture showed significantly lower abundance of uptake hydrogenase (42.6543 fold), formate dehydrogenase (44.6645 fold) and significantly higher abundance of proteins related to acetate metabolism (i.e. GltA; 61.66 62 fold) compared to GS pure culture. Moreover, SF in the SF-GS coulture showed significantly lower abundance of IET related formate dehydrogenases, Fdh3 (69.1851 fold) and Fdh5 (20.4229 fold), although and the rate of propionate conversion in SF-GS was nineeight-fold lower than in the SF-MH coculture. In contrast, compared to GS pure culture, we found lower abundance of pilus-associated cytochrome OmcS (2.14 fold) and piliA (5.37 fold) in the SF-GS coculture that is suggested to be necessary for DIET. Furthermore, neither visible aggregates formed in the SF-GS coculture, nor the pili-E of SF (suggested as e-pili) were detected. These findings suggest that the IET mechanism is complex in the SF-GS coculture, and can be mediated by several mechanisms rather than one discrete pathway. Our study can be further useful in understanding syntrophic propionate degradation in bioelectrochemical and anaerobic digestion systems.